Design and fabricate a temperature sensor on aluminium using tilting furnace / Muhammad Fikhran Hamsyi Azmi - Azmi, Muhammad Fikhran Hamsyi (2022)
This Final Year Project (FYP) is to design and fabricate a temperature sensor on aluminium using tilting furnace. The main purpose of this study is to develop and manufacture a temperature sensor using a tilting furnace on aluminum. Thermal sensors have been intensively developed and used in a wide range of applications, from monitoring of industrial processes to environmental control. The wire will be connected to the temperature sensor. When the temperature of the molten aluminum in impact reaches a high temperature, it allows it to make a warning sound. The sensor will detect temperature changes and provide an output on the monitor. Heat is produced by the movement of molecules and atoms, and the greater the movement, the more heat is produced. Temperature sensors detect the quantity of heat energy or even coldness generated by an object or system, allowing us to detect temperature changes. This temperature sensor can be used in industries like foundries and metal casting